Conceptual Framework and Research Approaches to Motivation to Learn - Danailova, Irina (Research Papers, 2019)
The main purpose of this report is to follow the concept of "learning motivation" in time and in different theories, thus convincingly showing how complex and meaningful is the question of "what motivates a person to learn" and how complex and difficult is to find a single answer. The problems with knowledge acquisition, motivation to learn are subject to research interest because of their practical and applied significance.